(untitled) (Research, Society and Development, 2024)
The Bolton method determines the proportion between the mesiodistal widths of the maxillary and mandibular teeth, using a formula that indicates whether there is any discrepancy in size between the elements. However, some factors such as genetics and type of malocclusion can affect this proportion. The professional can compensate for tooth disproportion when carrying out orthodontic planning, through removals and/or additions to dental structures and also changes in angles and inclinations. The present study aimed to analyze the presence of Bolton discrepancy in patients scanned for orthodontic documentation in a radiological clinic in Pindamonhangaba, SP – Brazil. Bolton proportions were calculated in millimeters for the 10 patients, applying the formula of anterior and general proportions, subtracting the results from the existing sums of the mesiodistal width of the teeth, both upper and lower. The total corrections for the anterior and general proportions were determined using a specific formula and converted to millimeters. It was possible to observe that all patients randomly assigned by the clinic had Bolton discrepancies, suggesting a strong presence of the condition in the population, which may be related to the great mix of genetics present in Brazilian territory. The limitations of the study were the small sample size and the scarce current literature on the topic, suggesting larger samples for future work to update the subject.